Virus-Induced Silencing of Key Genes Leads to Differential Impact on Withanolide Biosynthesis in the Medicinal Plant, Withania somnifera. (20th November 2017) - Agarwal, Aditya Vikram; Singh, Deeksha; Dhar, Yogeshwar Vikram; Michael, Rahul; Gupta, Parul; Chandra, Deepak; Trivedi, Prabodh Kumar
Abstract: Withanolides are a collection of naturally occurring, pharmacologically active, secondary metabolites synthesized in the medicinally important plant, Withania somnifera. These bioactive molecules are C28-steroidal lactone triterpenoids and their synthesis is proposed to take place via the mevalonate (MVA) and 2-C-methyl-d-erythritol-4-phosphate (MEP) pathways through the sterol pathway using 24-methylene cholesterol as substrate flux. Although the phytochemical profiles as well as pharmaceutical activities of Withania extracts have been well studied, limited genomic information and difficult genetic transformation have been a major bottleneck towards understanding the participation of specific genes in withanolide biosynthesis. In this study, we used the Tobacco rattle virus (TRV)-mediated virus-induced gene silencing (VIGS) approach to study the participation of key genes from MVA, MEP and triterpenoid biosynthesis for their involvement in withanolide biosynthesis. TRV-infected W. somnifera plants displayed unique phenotypic characteristics and differential accumulation of total Chl as well as carotenoid content for each silenced gene suggesting a reduction in overall isoprenoid synthesis. Comprehensive expression analysis of putative genes of withanolide biosynthesis revealed transcriptional modulations conferring the presence of complex regulatory mechanisms leading to withanolide biosynthesis. In addition, silencing of genes exhibited modulated total and specific withanolide accumulation at different levels as compared with control plants. Comparative analysis also suggests a major role for the MVA pathway as compared with the MEP pathway in providing substrate flux for withanolide biosynthesis. These results demonstrate that transcriptional regulation of selected Withania genes of the triterpenoid biosynthetic pathway critically affects withanolide biosynthesis, providing new horizons to explore this process further, in planta.